Analisis Faktor-Faktor Usaha Berkelanjutan bagi UMKM di Kabupaten Bengkulu Tengah - arnova, Iwin (Penerbit Goodwood, 2022)
Purpose: of this study was to analyze the business capital, technology, quality, and education of Micro, Small and Medium Enterprises of Karya Rattan Bengkulu. Methods: The sampling technique used a saturated sample of 30 people. The type of data used is primary data in the form of questionnaires and interviews. This research was conducted at the Micro, Small and Medium Karya Rattan, Central Bengkulu. Results: The study found that the source of capital from Karya Rattan came from their own capital which was established in 2017 amounting to Rp. 7500.000,-. The capital that continues to grow from the sales makes Karya Rattan grow. The resulting products are of high quality and have a long service life, are highly varied and innovative. Through good quality, Rattan works have been able to last for 5 years until now. Limitation: This research is that it only examines 1 Micro, Small and Medium in Central Bengkulu. Its contribution Rattan work has provided economic progress for the Micro, Small and Medium sector, which in addition to increasing its income also has an impact on increasing business in Central Bengkulu. Contribution: Research can increase knowledge about Micro, Small and Medium especially in the furniture sector.